Delegation and Decentralization in Abdicating Authority and Upholding Ubuntu Philosophy in Social Welfare Organisations: A Critical and Theoretical Perspectives - Tariro Portia Tendengu (Research Aspects in Arts and Social Studies Vol. 3, 2022)
The purpose of this paper is to augment on the critics of delegation and decentralization in abducting authority and upholding Ubuntu philosophy in Social Welfare Organisations in Zimbabwe. In abdicating authority and upholding Ubuntu Philosophy, the systematic distribution of authority by top management in social welfare organisations remains a contentious issue. Delegating responsibility while abdicating respect and human dignity is a critical issue in social welfare organisations, as some community-based organisations fail to consider the inherent worth of employees before undertaking projects and assigning tasks. In governmental parastatals participatory democratic values are not effectively implemented when delegating duties, the top management restricts itself to major decisions areas like policy making, coordination and control. The lower level managers have enough decision making authority and support to introduce innovativeness in their work. Data collection methods that were used included observations, focus group discussions and interviews. The targeted population included international, statutory and non-statutory organisations in Zimbabwe. The study concluded that delegation and decentralisation in social welfare organisations are criticised as a result of local beurocracy and inequalities that exist in organisations. Respondents stated that decentralisation is a significant hindrance in upholding organisational values and ethics. Some executives in social welfare organisations do not understand the basic need for basic respect and compassion for other employees, such as sharing decision-making responsibility.